#TITLE_ALTERNATIVE# - REYNOLD TJIA (NIM : 132 06 032); Dosen pembimbing : Prof. Dr. Ir. Bambang Riyanto T., M.Sc, HAROLD
Active Noise Control (ANC) is a system using the wave destructive superposition principle that reduces noise signal, achieved by generating an anti noise signal, a signal has opposite phase from noise signal. An ANC system is very effective to cancel low frequency noise signal and appropriate to work with Passive Noise Cancellation (PNC) which is effective to cancel high frequency noise signal. ANC and PNC system produce a complete noise canceling Passive and Active Noise Control (PANC) system. In this Final Task, the implementation of the multiple-channel decentralized and centralized ANC system used a TMS320C6713 DSP Starter Kit with FxLMS and FxNLMS adaptive algorithm. The ANC system was done in a small enclosure with a car’s machine noise signal. The experimental results show that maximum attenuation was 3.5-3.8 dBA produced by the 1 × 4 × 4 decentralized ANC system with 64 order of secondary filter and 64 order of adaptive filter using FxNLMS algorithm.